KEMANDIRIAN BELAJAR, ADVERSITY QUETIONT DAN KEMAMPUAN PENALARAN MATEMATIS PADA IMPLEMENTASI PEMBELAJARAN DARING MATAKULIAH ANALISIS REAL - Muhamad Farhan; Arif Rahman Hakim (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2021)
This research aims at revealing the effect of self-regulated learning and adversity quotient towards mathematical reasoning abilities. This type of research is a survey method. The population in this study were students of the mathematics education study program at Indraprasta University PGRI Jakarta who programmed real analysis courses in the sixth semester and the research sample was 25 students. The instruments in this research were test and non-test instruments. Data instruments test the ability of mathematical reasoning from the daily test scores of students through the description questions as many as 6 questions and Data instruments are a non-test instrument in the form of a self-regulated learning and adversity quotient scale questionnaires. The data analysis technique used is multiple regression analysis with SPSS 16.0. The results showed that (1) self-regulated learning and adversity quotient simultaneously have a significant effect on mathematical reasoning ability by 26.6% while 73.4% is influenced by other variables not examined, (2) self-regulated learning has a significant effect on the ability of mathematical reasoning by 26.5%, (3) adversity quotient does not have a significant effect on mathematical reasoning ability.